Keefektifan Poly Aluminium Chloride (Pac) Dalam Menurunkan Kadar Biological Oxygen Demand (Bod) Limbah Cair Rumah Makan - Galih, Vera Nalurining (2016)
dissolved in water. BOD levels at Fadhila Restaurant in Mencoraya Gonilan Kartasura already exceeded the quality standards thats 716,56 mg/l. According to the Central Java Provincial Regulation No. 5 of 2012 on Domestic Wastewater Quality Standard of 100 mg/l. The purpose of this study to determine the effectiveness of poly aluminium chloride (PAC) in lowering levels of effluent BOD restaurant by adding PAC with 250 mg/l, 500 mg/l and 750 mg/l. This research method True Experiment with Pretest and Posttest study design with Control Group. The sampling technique used quota sampling. Statistical tests used of One Way Anova. The results showed difference between the reduction in BOD levels before and after treatment in restaurants wastewater with coagulant PAC (p = 0.000). The most effective dose in lowering levels of BOD in the restaurant wastewater is 500 mg / l with a decrease (80.64%).